Documentos presentados a la Séptima Conferencia Regional sobre la Integración de la Mujer en el Desarrollo Económico y Social de América Latina y el Caribe = Documents presented at the Seventh Session of the Regional Conference on the Integration of Women into the Economic and Social Development of Latin America and the Caribbean - NU. CEPAL (CEPAL, 2014)
Publicación bilingüe